2016
DOI: 10.2196/jmir.6414
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile App to Stabilize Daily Functional Activity of Breast Cancer Patients in Collaboration With the Physician: A Randomized Controlled Clinical Trial

Abstract: BackgroundThe well-being of breast cancer patients and reporting of adverse events require close monitoring. Mobile apps allow continuous recording of disease- and medication-related symptoms in patients undergoing chemotherapy.ObjectiveThe aim of the study was to evaluate the effects of a mobile app on patient-reported daily functional activity in a supervised and unsupervised setting.MethodsWe conducted a randomized controlled study of 139 breast cancer patients undergoing chemotherapy. Patient status was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
153
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(153 citation statements)
references
References 12 publications
(16 reference statements)
0
153
0
Order By: Relevance
“…There are few published studies that have utilized smartphone applications as part of interventions aimed at altering health behaviors in a population of cancer patients or survivors. Most of this published literature has focused on interventions designed to enhance disease management—ranging from appointment reminders, to applications to aid in symptom recording to enhance subsequent patient‐doctor discourse, to education regarding the patient's diagnosis and treatment—or to promote adherence to dietary and physical activity guidelines . Although these studies were limited by small sample sizes and short follow‐up periods, the efficacy of mHealth interventions was consistently reported in terms of better management and delivery of cancer care, improved physical activity, and more healthy living.…”
Section: Discussionmentioning
confidence: 99%
“…There are few published studies that have utilized smartphone applications as part of interventions aimed at altering health behaviors in a population of cancer patients or survivors. Most of this published literature has focused on interventions designed to enhance disease management—ranging from appointment reminders, to applications to aid in symptom recording to enhance subsequent patient‐doctor discourse, to education regarding the patient's diagnosis and treatment—or to promote adherence to dietary and physical activity guidelines . Although these studies were limited by small sample sizes and short follow‐up periods, the efficacy of mHealth interventions was consistently reported in terms of better management and delivery of cancer care, improved physical activity, and more healthy living.…”
Section: Discussionmentioning
confidence: 99%
“…A sample of 108 participants (54 participants per group) was needed to detect an effect size of at least 0.60, with 80% power, two-sided P<.05, and 20% attrition. A dropout rate of 10-20% were reported in previous studies involving an app-based study [9,24]. Finally, the recruitment numbered 114 participants in total (57 participants per group).…”
Section: Sample Size Calculationmentioning
confidence: 88%
“…This would permit remote monitoring of patients with fatigue through an online system, which could incorporate evidence‐based practice and guidelines to monitor and improve fatigue throughout the treatment of cancer. Related research using mobile apps has found positive experiences for patients with cancer and HCPs (Egbring et al, 2016; Rincon et al, 2017; Young‐Afat et al, 2016). In Oman, smartphone use has increased by 154% over the last 3 years (Ministry of Transport and Communications, 2017), with most of the population having a smartphone.…”
Section: Discussionmentioning
confidence: 99%